Performance Analysis of an Alkaline Fuel Cell with Ni/C on the Anode - Nasrul Ilminnafik,; Raafi Aditya Nugraha,; Mohammad Rifqy Alfariz,; Digdo Listyadi Setyawan,; Muhammad Khadafi Ibnu, (International Journal of Integrated Engineering, 2026)
Increasing global energy demand encourages the development of renewable energy, one of which is hydrogen-based energy through fuel cells. Alkaline fuel cell (AFC) is an attractive alternative because it can use non-noble metal catalysts. This research aims to develop an economical nickel-based catalyst material for the anode of an AFC. Experiments were conducted by mixing nickel and carbon black (Ni/C) as supporting materials, and polytetrafluoroethylene as a binder. The nickel concentration variations used were 0%, 10%, and 20% by weight. Results show that increasing nickel concentration is directly proportional to AFC performance. Cells with 20% nickel concentration produced the highest voltage, current, and efficiency. This research proves the potential of nickel as an effective and economical alternative catalyst in the development of AFCs, which can contribute to the advancement of renewable energy technology.